1992
DOI: 10.1021/bi00162a007
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin receptor activating peptides: importance of the N-terminal serine and its ionization state as judged by pH dependence, nuclear magnetic resonance spectroscopy, and cleavage by aminopeptidase M

Abstract: Peptides derived from the recently identified thrombin receptor were tested for their ability to induce platelet aggregation in platelet-rich plasma. The 14 amino acid peptide identified as the new N-terminus after thrombin cleavage (T-14) and an 11 amino acid peptide (T-11) lacking the 3 C-terminal amino acids of T-14 were studied. Both induced platelet aggregation at micromolar concentrations, with T-11 about twice as potent as T-14. Induction of platelet aggregation by these two peptides showed an unusual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
2

Year Published

1993
1993
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 47 publications
2
54
2
Order By: Relevance
“…Thus, these observations establish the specificity of the PAR-2 ligand for its receptor and exclude the possibility that endothelial cell responses are mediated by trans-activation of the TR. Indeed, these observations are consistent with previous TR structure-function studies demonstrating the importance of the phenylalanine in position 2 of the Tr-activating peptide (TR [42][43][44][45][46][47] ) to affect receptor activation (6)(7)(8). Furthermore, the inability of TR antisense oligonucleotides to affect PAR [39][40][41][42][43][44] -mediated responses excludes the possibility that the cell-surface coexpression of both receptors are physically linked or dually required for optimal activation-dependent responses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, these observations establish the specificity of the PAR-2 ligand for its receptor and exclude the possibility that endothelial cell responses are mediated by trans-activation of the TR. Indeed, these observations are consistent with previous TR structure-function studies demonstrating the importance of the phenylalanine in position 2 of the Tr-activating peptide (TR [42][43][44][45][46][47] ) to affect receptor activation (6)(7)(8). Furthermore, the inability of TR antisense oligonucleotides to affect PAR [39][40][41][42][43][44] -mediated responses excludes the possibility that the cell-surface coexpression of both receptors are physically linked or dually required for optimal activation-dependent responses.…”
Section: Discussionsupporting
confidence: 90%
“…This irreversible cleavage reveals a new amino terminus that functions as a "tethered ligand," presumably binding intramolecularly to other receptor domain(s) to effect downstream receptor coupling events (1,4,5). Synthetic peptidomimetics, based on the new amino terminus created after cleavage, function as full agonists for receptor activation, bypassing the need for proteolytic receptor activation (1,(6)(7)(8). Elucidation of receptor domains involved in ligandmediated receptor activation have been identified in this and other laboratories (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…This proteolytic switch removes amino-terminal sequence that sterically hinders ligand function and generates a new protonated amino group at the amino terminus created by receptor cleavage. In the SFLLRN peptide, the cognate protonated amino group is critical for agonist activity (7,8). Parallels with zymogen activation in serine proteases are apparent (2, 9).…”
Section: How Does a Protease Talk To A Cell?mentioning
confidence: 99%
“…Recently, Coller et al have demonstrated that aminopeptidase M in plasma and on endothelial cells cleaves and thereby inactivates TRAP [19]. Accordingly, inhibition of aminopeptidase M enhances platelet aggregation induced by TRAP pointing to the possibility of rapid degradation of TRAP in in vivo and in vitro systems.…”
Section: Introductionmentioning
confidence: 99%